EFFECT OF LOW-DENSITY LIPOPROTEIN (LDL) CHOLESTEROL VALUE ON NON-PROLIFERATIVE DIABETIC RETINOPATHY (NPDR) IN PATIENTS WITH TYPE II DIABETES MELLITUS (T2DM): A SYSTEMATIC REVIEW: Poster Presentation - Observational Study - General practitioner - Nugraha, Satria Budi; Siahaan Sp. M, dr. Yoseph M.P.A. (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Type 2 Diabetes Mellitus (T2DM) is a metabolic disease in which the body is unable to control blood sugar levels and is characterized by hyperglycemia caused by lack of insulin action. One of the most common microvascular complications of DM that can cause blindness to sufferers is Diabetic Retinopathy (DR). One of the risk factors that can exacerbate the progression of T2DM is the level of Low-Density Lipoprotein (LDL). However, there are still differences of opinion in several studies if LDL has a significant role in the occurrence of DR. This study aimed to determine whether there is a relationship between the value of LDL cholesterol and the occurrence of Non-Proliferative Diabetic Retinopathy. Methods : Systematic review utilizing MeSH terminology and PICO methods were done for information extraction of online database, including PubMed, and Google Scholar by utilizing the following keyword “Low-Density Lipoprotein”, “Non-Proliferative Diabetic Retinopathy”, “Diabetes Melitus”. The extracted studies were then analyzed using the New-Castle Ottawa Scale (NOS). Results : In total, 2 eligible studies (103 subjects) were found. Dornan et al., stated that total cholesterol levels were higher in NPDR Patients (5.1 +/- 0.7 mmol/l, p ? 0,02) and Mursi et al., shows that in patients with uncontrolled LDL cholesterol, NPDR was found (53,7%, p < 0,015). NOS was used to evaluate the quality of the studies and all studies showed to be in good quality. Conclusion : According to the results of this systematic review, there is a significant correlation between the degree of diabetic retinopathy and LDL cholesterol.